Functions of transforming growth factor-β isoforms in the nervous system: cues based on localization and experimental in vitro and in vivo evidence - Unsicker, Klaus; Strelau, Jens (EJB, 2000)
This review briefly describes the cellular distribution and documented roles of the transforming growth factor (TGF)-β isoforms TGF-β2 and -β3 in the central and peripheral nervous system. TGF-β2 and -β3 are coexpressed in developing radial glial and mature astroglial and Schwann cells, as well as in subpopulations of differentiated neurons, most prominently in cortical, hippocampal, and brainstem/spinal cord motor neurons. In vitro studies have suggested a number of potential, physiologically relevant functions for TGF-βs including regulation of astroglial cell proliferation, expression of adhesion molecules, survival promoting roles for neurons in combination with established neurotrophic factors, and differentiative actions on neurons.